2011
DOI: 10.1002/app.33935
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of novel biodegradable poly(butylene succinate) copolyesters composing of isosorbide and poly(ethylene glycol)

Abstract: A series of biodegradable isosorbide-based copolyesters poly(butylene succinate-co-isosorbide succinate-co-polyethyleneoxide succinate) (PB x I y E z S) were synthesized via bulk polycondensation in the presence of dimethyl succinate (DMS), 1,4-butanediol (BDO), poly-(ethylene glycol) (PEG) and isosorbide (ISO). The crystallization behaviors, crystal structure and spherulite morphology of the copolyesters were analyzed by differential scanning calorimetry (DSC), wide angle X-ray diffraction (WAXD) and polarizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…16,27 It will be worth therefore to compare Is with Glux and Manx regarding thermal properties. Unfortunately only a few papers dealing with PBS copolyesters containing isosorbide are found in the accessible literature, 28,29 and data there afforded are incomplete or not fully suitable for a reliable comparison. Noordover et al 16b reported low molecular weight PIsS with T g between $50 and $70 C and Tan et al 29 described the a PB 11 Is 89 S copolyester with M n 14 000 and T g of $45 C. More recently, Jacquel et al 29 succeeded in preparing PB x Is y S copolyesters with astonishingly high molecular weights (45 000 < M n < 55 000) although with compositions restricted to low contents in Is (less than 15 mole%).…”
Section: Sugar-based Bicyclic Diols Comparedmentioning
confidence: 99%
“…16,27 It will be worth therefore to compare Is with Glux and Manx regarding thermal properties. Unfortunately only a few papers dealing with PBS copolyesters containing isosorbide are found in the accessible literature, 28,29 and data there afforded are incomplete or not fully suitable for a reliable comparison. Noordover et al 16b reported low molecular weight PIsS with T g between $50 and $70 C and Tan et al 29 described the a PB 11 Is 89 S copolyester with M n 14 000 and T g of $45 C. More recently, Jacquel et al 29 succeeded in preparing PB x Is y S copolyesters with astonishingly high molecular weights (45 000 < M n < 55 000) although with compositions restricted to low contents in Is (less than 15 mole%).…”
Section: Sugar-based Bicyclic Diols Comparedmentioning
confidence: 99%
“…The X c value of PCL- b -PIS also decreases from 45 to 28% as the content of PIS increases from 0 to 30 wt %. These results illustrate that the incorporation of PBG or PIS into the main chain of PCL depresses the crystallization of PCL, which can be ascribed to their asymmetric structures. However, the depressing effect of PBG is lower than that of PIS. This phenomenon is also found by other researchers, , i.e., they have found that diacetalized hexitols derived from d -glucitol appear to be more favorable than Is or 2,4:3,5-di- O -methylene- d -mannitol to maintain crystallinity.…”
Section: Resultsmentioning
confidence: 81%
“…During degradation test, water uptake and hydrophilic were important because ester group could contact with water and then occur depolymerization. 19,28 In this paper, the water contact angel and water uptake of PBSD copolymers were analyzed. The water contact angel of PBS was 89.0 ± 2.3 , while, PBSD showed high hydrophilicity with 55.6 ± 1.3 .…”
Section: Surface Hydrophilicity Of Pbsd Copolymersmentioning
confidence: 99%